Evidance Based Pracrice Terapi Rendam Kaki Menggunakan Air Hangat Terhadap Penurunan Tekanan Darah - Nindi, Engryne; Londok, Sefni (JURNAL ILMIAH KESEHATAN MANADO, 2025)
Hypertension is a "silent killer", with 1 in 3 people with hypertension in Indonesia not realizing that they have hypertension. This persistent increase in blood pressure is positively correlated with an increased risk of heart disease, kidney failure and stroke. It is necessary to check regularly and periodically, so that it can be detected early so that early treatment can be carried out, so that complications can be avoided and disability and death can be prevented. By carrying out early detection and checking blood pressure every month, it is hoped that complications due to hypertension can be prevented and controlled. Hypertension treatment can be done in 2 ways, namely pharmacological and non- pharmacological treatment, in this case soaking the feet in warm water. Soaking your feet in warm water will widen the blood vessels so that blood circulation becomes smooth, which can lower blood pressure. The aim of this scientific work is to implement foot soak therapy using warm water to reduce blood pressure in Mrs. S.P in Bahu Lingk.1 Manado. The results of research using evidence-based nursing foot soak therapy using warm water which was carried out for 3 days, the evaluation results showed that foot soak therapy using warm water was effective in lowering blood pressure in Mrs. S.P. Conclusion: this scientific work shows a decrease in blood pressure in Mrs. S.P with hypertension after being given foot soak therapy using warm water. Suggestion: to all health workers to provide action and education on providing foot soak therapy using warm water to clients who suffer from hypertension.